Lipoblastoma and lipomatosis in children-case report - Rasha Kassem; Ahamed Faiz; Sunil Yadav Kumar; Sam Aruputha John; Ola Taher; Aisha S. Khan (Elsevier, 2017)
Lipoblastoma (Encapsulated) and Lipoblastomosis (Diffusely infiltrating tumor) are rare benign mesenchymal tumors of embryonic fat. It occurs exclusively in infants and children less than 3 years of age. The extremities are the most common sites of occurrence. These lipomatous lesions are fast growing tumors which need proper evaluation and surgical management to avoid mutilating surgery. We report two cases of lipomatous tumors in children, 5 year old boy with lower anterior abdominal parietal wall swelling and another 4 year old girl with swelling in the lateral chest wall. Clinically the lesions were subcutaneous, mobile and soft with ill-defined edges. Both of these tumors were excised completely. Histopathology of these lesions showed lipoblastomosis and lipoblastoma respectively.